Bond Stress between Steel-Reinforced Bars and Fly Ash-Based Geopolymer Concrete - Yifei Cui; Peng Zhang; Jiuwen Bao (Advances in Materials Science and Engineering)
Geopolymer concrete has been regarded as one of the most important green construction materials, which has been restrained in engineering applications partially due to a lack of bond studies. The structural performance of the reinforced concrete components primarily relies on the sufficient bond between the concrete and the reinforcing bars. Before being utilized in any concrete structure, GPC must demonstrate that it possesses understandable bond behaviour with commercial steel reinforcements. This work presents an experimental investigation on the bond stress of steel bars in reinforced geopolymer concrete (GPC) structures. Standard beam-end pull-out tests were conducted on GPC specimens reinforced with 16 mm plain and ribbed bars that were equipped with electrical resistance strain gauges. The longitudinal variation in the bond stress in the GPC beams during the pull-out tests was calculated and plotted, as well as the stress in steel bars. The cracks on the bond area of the GPC were compared with those of the corresponding ordinary Portland cement concrete (OPC), as well as the steel stress and bond stress. The results showed that the relative slip between plain bar and geopolymer concrete varies from 30–450 microns from the loaded end to the free end when the bond stress decreased by 83%. The relative slip between ribbed bar and geopolymer concrete varies from 280–3,000 microns from the loaded end to the free end when the bond stress decreased by 57%. Generally, GPC is different from OPC in terms of bond stress distribution.